2013
DOI: 10.1016/j.molcel.2013.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic Acid Activates DNA Damage Responses to Potentiate Plant Immunity

Abstract: SUMMARY DNA damage is normally detrimental to living organisms. Here we show that it can also serve as a signal to promote immune responses in plants. We found that the plant immune hormone salicylic acid (SA) can trigger DNA damage in the absence of a genotoxic agent. The DNA damage sensor proteins, RAD17 and ATR, are required for effective immune responses. These sensor proteins are negatively regulated by a key immune regulator SNI1 (suppressor of npr1-1, inducible 1), which we discovered as a missing subun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
162
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(171 citation statements)
references
References 34 publications
(56 reference statements)
9
162
0
Order By: Relevance
“…Also, DNA repair proteins have been shown to be directly involved in the regulation of gene expression during plant defense responses (Song et al, 2011). The DNA damage response is an intrinsic component of the plant immune response and, in turn, enhances salicylic acid-mediated defense gene expression (Yan et al, 2013). Among the Ustilaginales, which cause characteristic floral symptoms in the immature, proliferative host floral organs, U. maydis is the only species that causes local tumors in vegetative tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Also, DNA repair proteins have been shown to be directly involved in the regulation of gene expression during plant defense responses (Song et al, 2011). The DNA damage response is an intrinsic component of the plant immune response and, in turn, enhances salicylic acid-mediated defense gene expression (Yan et al, 2013). Among the Ustilaginales, which cause characteristic floral symptoms in the immature, proliferative host floral organs, U. maydis is the only species that causes local tumors in vegetative tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it will be intriguing to study the role of SOG1 in response to pathogens. Recent studies have revealed that the DDR and immune responses are closely related in plants (Yan et al, 2013;Song and Bent, 2014). Since SOG1 may also play a crucial role in the plant immune system, it is imperative to examine whether the sog1-1 mutation affects sensitivity to various pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, a relationship between the plant immune response and DNA damage has been reported recently. Yan et al (2013) showed that the plant immune hormone salicylic acid triggers DNA damage in the absence of a genotoxic agent, and the DDR factors ATR and RAD17 are required for effective immune responses. Furthermore, microbial pathogens reportedly induce DSBs in A. thaliana genomic DNA (Song and Bent, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…While SA is essential for SAR development, it needs to be maintained at low levels in parts of the plant other than the site of hypersensitive response to avoid harmful effects, such as growth retardation (Rivas-San Vicente and Plasencia, 2011), DNA damage (Yan et al, 2013), and physiological disturbance (Scott et al, 2004). In this view, it is envisioned that SA serves as an initiating signal that links local infection with the induction of SAR in distal tissues; therefore, high levels of SA would not be necessarily required for the NPR1 activation.…”
Section: Convergence Of Sa and Snrk28-mediated Signals At Npr1mentioning
confidence: 99%